2017
DOI: 10.3390/polym9030087
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Investigation of α-Keratin Fibers as Multi-Coupled Stimuli of Responsive Smart Materials

Abstract: Like the water responsive shape memory (SM) effect of β-keratin bird feathers, α-keratin hairs either existing broadly in nature are found responsive to many types of coupled stimuli in SM behaviors. In this article, α-keratin hairs were investigated for the combined stimuli of thermo-solvent, solvent-solvent, and UV (radiation)-reductant sensitive SM abilities. The related netpoints and switches from the hair molecular networks were identified. The experimental results showed that α-keratin hairs manifested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Recently, researchers investigated the effect of water on the shape memory of animal hairs, such as that of sheep, goats, and camels, and on the variations of the crystal, disulfide, and hydrogen bonds in the macromolecules and reported that the wool fibers exhibit water-responsive SME. [17] Clothing materials generally have a hierarchical structure because of the twisting of fibers into yarns and the knitting or weaving of yarns into fabrics. Besides wool fiber, the water responsiveness of a hydrogel-coated wool yarn was investigated; [18] however, the materials exhibited a poor response time because of slow water diffusion.…”
Section: Two-way Shape Memory Of Wool Yarnsmentioning
confidence: 99%
“…Recently, researchers investigated the effect of water on the shape memory of animal hairs, such as that of sheep, goats, and camels, and on the variations of the crystal, disulfide, and hydrogen bonds in the macromolecules and reported that the wool fibers exhibit water-responsive SME. [17] Clothing materials generally have a hierarchical structure because of the twisting of fibers into yarns and the knitting or weaving of yarns into fabrics. Besides wool fiber, the water responsiveness of a hydrogel-coated wool yarn was investigated; [18] however, the materials exhibited a poor response time because of slow water diffusion.…”
Section: Two-way Shape Memory Of Wool Yarnsmentioning
confidence: 99%
“…dry) can be converted to each other, judging from their IR characteristic peaks in shifting of wavenumber and variation of peak intensity ratio. This indicates the switch role of hydrogen bond for controlling the hair crimping shape [32].…”
Section: Resultsmentioning
confidence: 99%
“…38 As shown in Figure 3(b), the intrinsic black color of the CNT would darken the color of the PVA/CNT hydrogel when comparing with the neat PVA matrix in relevant FE-SEM micrographs. 39 The freezing-thawing process cycle is an effective way to build a porous hydrogel structure. 40,41 Theoretically, as the number of freezing-thawing cycles increases, the density of hydrogen bonds increases, due to the formation of the crystalline phase.…”
Section: Shape Memory Behaviormentioning
confidence: 99%
“…40,41 Theoretically, as the number of freezing-thawing cycles increases, the density of hydrogen bonds increases, due to the formation of the crystalline phase. 39,42 The wall thickness of the pores in hydrogels was measured with Image J analyzer for 10 random points. The average pore wall thickness was obtained 1.012 μm, and the interconnections are established.…”
Section: Shape Memory Behaviormentioning
confidence: 99%